Mesenchymal stem cell conditioned medium azacytidine, panobinostat and GSK126 alleviate TGF-β-induced EMT in lung cancer - SHEN,Huihui (2022)
Abstract This study aimed to investigate the effects of mesenchymal stem cells (MSCs) conditioned medium, azacytidine, panobinostat, and GSK126 on TGF-β-induced EMT in lung cancer. MSC were cultured in DMEM medium to make MSC conditioned medium. Our results showed that MSC conditioned medium, azacytidine, panobinostat and GSK126 reduced cell viability, invasion, expressions of N-cad, vimentin and α-SMA and increased E-cad expression in cells treated with TGF-β. MSC conditioned medium alleviated TGF-β-induced increases in cell viability and decrease in E-cad expression. In conclusion, MSC conditioned medium, azacytidine, panobinostat, and GSK126 could alleviate TGF-β-induced EMT in lung cancer.